Final project new interior design scheme of Koko Cafe for Malaysia Coco Board at Jalan Changkat Bukit Bintang, Kuala Lumpur / Emma Abd Nasir - Abd Nasir, Emma (Faculty of Architecture, Planing and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to Proposed New Interior Design Scheme of Koko Cafe for Lembaga Koko Malaysia that is situated at 14&16, Jalan Changkat Bukit bintang, Kuala Lumpur. This proposed cafe is to create a new identity of design for local cocoa product in order to attract local customer and tourists to try the variety of food based on local cocoa, at the same time to promote local cocoa product successfully in the international market. The target market of this cocoa product is the chocoholic and a person who loves to try variety tastes from cocoa based. The concept must represent the client itself, but at the same time it would increase the faith in the customers and the chocoholic lovers about the local cocoa product. The interior design for Koko Cafe is based on Moden concept. This is to full fill the client’s needs as they want the Koko Cafe to have the look emphasis the delicious of chocolate character and at the same time blande with the modern playfulness design that would attract the customers with different image that they would only get in Koko Cafe. Before getting a desired design that is suitable with the client’s needs, some data analysis should be done where these analysis is on types of customers to attend the session, types of services offered, products of the brand, spaces to be concluded in the proposed area, operation time and informations about other cafe or restaurant that use the same system in management, as the proposed cafe. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.